(untitled) (Conference Zone, 2022)
Advanced foreign experience shows that the development of cashless payment practices on the basis of innovations is a prerequisite for the development of national payment systems. One of the important innovations in the practice of cashless payments is the conversion of checks. Conversion of checks significantly reduces the costs associated with clearing paper checks. However, banks still need a paper version of the check. This is because they have to keep the paper version of the check as a daily document. Another innovation in the practice of cashless payments is the electronic submission and payment of accounts.